2012
DOI: 10.5301/ejo.2011.8434
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsificator and Sterile Drapes Contamination during Cataract Surgery: A Microbiological Study

Abstract: Evaluation of intraoperative fluids can provide evidence on sources or vehicles of postsurgical infections. Antibiotic prophylaxis and topical povidone-iodine can significantly contribute to minimize the risk of endophthalmitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In spite of using preoperative antibiotics and povidone-iodine and following careful sterilization and aseptic protocols, the rate of intraocular bacterial contamination has shown to be as high as 31%. [ 28 ] Injecting antibiotics intracamerally at the end of surgery is intended to kill bacterial microbes that have been introduced during the procedure. Posterior capsular rupture is one of the strongest risk factors for infectious endophthalmitis.…”
Section: Intracameral Antibiotics During Cataract Surgerymentioning
confidence: 99%
“…In spite of using preoperative antibiotics and povidone-iodine and following careful sterilization and aseptic protocols, the rate of intraocular bacterial contamination has shown to be as high as 31%. [ 28 ] Injecting antibiotics intracamerally at the end of surgery is intended to kill bacterial microbes that have been introduced during the procedure. Posterior capsular rupture is one of the strongest risk factors for infectious endophthalmitis.…”
Section: Intracameral Antibiotics During Cataract Surgerymentioning
confidence: 99%
“…Microbiological examinations have shown that the rate of contamination of the surgical fluids is high (up to 50%) in spite of preoperative cleaning of the conjunctiva with povidone‐iodine and preoperative use of topical antibiotic (Balestrazzi et al. ). The rate of positive samples from the anterior chamber is usually <5% (Parmar et al.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the administration of antibiotics and povidone-iodine before surgery and following the careful sterilization and aseptic protocols, bacterial contamination of the anterior chamber at the end of cataract surgery occurs in 20-40% of cases. [18][19][20][21][22] Moreover, evidence shows that postoperative bacterial endophthalmitis is commonly caused by exposure to bacteria from the external eye during or after cataract surgery. The etiologies of the aqueous fluid contamination during cataract surgery are as follows: the entry of multiple instruments may carry external ocular surface flora into the anterior chamber; incision leakage caused by poor or delayed wound healing may allow the retrograde influx of external surface fluid during and after surgery; contaminated surgical instruments or implants may induce infection.…”
Section: Discussionmentioning
confidence: 99%